COVID-19 and diabetic ketoacidosis misdiagnosed as primary anxiety: A case report on medical versus psychiatric causes of anxiety. - Rodríguez-León, Jamie (2021)
Anxiety disorders are of great importance in emergency psychiatry, both because of the frequency with which they occur, and because of the relevance of somatic diseases that can underlie an anxious condition. It is imperative to determine, from the initial diagnostic approach, whether the signs and symptoms of anxiety constitute either a response to stress, are manifestations of an underlying somatic pathology, or are explained as symptoms of a specific, primary psychiatric disorder. Currently, the COVID-19 pandemic --in which Peru has had the highest mortality rate in the world—is overwhelming the health services with complex and confusing pictures in which both the symptoms of the viral infection itself, as well as the of anxious reactions and stress responses are combined. On the basis of an illustrative case, in which the medical screening process was deficient and the patient was labeled as  a primary case of “anxiety”, with a regrettably ominous outcome, the literature about medical clearance is briefly reviewed, to categorically highlight the importance of a comprehensive and unbiased diagnostic consideration, based on well-developed and substantiated clinical criteria. On the other hand, the psychiatrist nowadays needs to be updated on the forms of psychopathological presentations associated with the symptoms of COVID-19.